2022
DOI: 10.1021/acs.jafc.2c00901
|View full text |Cite
|
Sign up to set email alerts
|

Protamine–Lipid–dsRNA Nanoparticles Improve RNAi Efficiency in the Fall Armyworm, Spodoptera frugiperda

Abstract: Developing safe and effective double-stranded RNA (dsRNA) delivery systems remains a major challenge for gene silencing, especially in lepidopteran insects. This study evaluated the protamine sulfate (PS)/lipid/dsRNA nanoparticle (NP) delivery system for RNA interference (RNAi) in cells and larvae of the fall armyworm (FAW), Spodoptera frugiperda, a major worldwide pest. A highly efficient gene delivery formulation was prepared using a cationic biopolymer, PS, and a cationic lipid, Cellfectin (CF), complexed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 64 publications
0
15
0
1
Order By: Relevance
“…In the case of the fall armyworm (Spodoptera frugiperda; Lepidoptera), the basic transcription levels of these core elements of RNAi machinery are similar to those observed in western corn rootworm (Diabrotica virgifera; Coleoptera) and southern green stink bug (Nezara viridula; Hemiptera) [39]. All three taxa are considered highly efficient species on which to employ RNAi strategies [40][41][42], from phylogenetic orders whose response to dsRNAi varies.…”
Section: Dsrna-mediated Silencing Core Machinerymentioning
confidence: 72%
“…In the case of the fall armyworm (Spodoptera frugiperda; Lepidoptera), the basic transcription levels of these core elements of RNAi machinery are similar to those observed in western corn rootworm (Diabrotica virgifera; Coleoptera) and southern green stink bug (Nezara viridula; Hemiptera) [39]. All three taxa are considered highly efficient species on which to employ RNAi strategies [40][41][42], from phylogenetic orders whose response to dsRNAi varies.…”
Section: Dsrna-mediated Silencing Core Machinerymentioning
confidence: 72%
“…Efforts have been made to increase the efficiency of RNAi, and a recent study indicated that chitosan nanoparticles and the Cellfectin II ( CFII ) transfection reagent helped dsRNA escape from endosomes and increased the RNAi response in S. frugiperda ( Ana et al, 2020 ; Gurusamy et al, 2020b ). The protamine-lipid-dsRNA nanoparticles, according to a more recent study by Dhandapani et al (2022) , increase RNAi efficiency in the target insect species S. frugiperda by shielding dsRNA from nuclease degradation and thereby significantly increasing the stability of dsRNA in the organism. Similarly, according to McGraw et al (2022) , clathrin-mediated endocytosis and macropinocytosis account for the majority of cellular uptake, and once inside the midgut, transcytosis is involved in moving branched amphipathic peptide nanocapsules (BAPCs) dsRNA from the lumen to the hemolymph of S. frugiperda .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), the basic transcription rate of the core elements of RNAi machinery presents similar levels to those registered to western corn rootworm (Diabrotica virgifera virgifera) Coleoptera and southern green stink bug (Nezara viridula) Hemiptera [40]). All of them are high RNAi efficient species [41][42][43] although represent phylogenetic orders whose response to dsRNAi varies. The impact of dsRNA exposition via injection or feeding in modulation of core genes, remains unclear.…”
Section: Dsrna-mediated Silencing Machinerymentioning
confidence: 99%